Exploring the Nexus of Islamic Modernism and Intellectual Development - Fauziah, Nur (SocioHumania: Journal of Social Humanities Studies, 2024)
This paper discusses Islamic modernism and the development of Islamic intellectualism. The method used is descriptive-analytical method with a historical approach. Its aim is to understand Islamic modernism and the development of Islamic intellectualism. The author finds that: First, Islamic modernism is a renewal of understanding that is more relevant to modern life, interpreting things to open the door of ijtihad and avoid blind adherence to schools of thought by thinking rationally in understanding and reflecting on Islamic teachings. Second, the development of Islamic intellectualism is divided into three eras. Each has a different pattern. The classical era began at the time of the Prophet Muhammad, where the development of Islamic intellectualism was practiced through teaching and education using methods of writing and memorization. In the medieval era, Islamic intellectualism began to flourish. Institutionalization began to emerge through theological movements, Sufism, and schools of thought. Furthermore, in the modern era, there is a struggle within Islamic intellectual tradition. The modern era seeks to eradicate superstition, myths, and innovations that have constrained the Muslim community.